2013
DOI: 10.1155/2013/181856
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Droplet Mass and Size Effect on Mist/Air Impingement Cooling Performance

Abstract: Impingement cooling has been widely employed to cool gas turbine hot components such as combustor liners, combustor transition pieces, turbine vanes, and blades. A promising technology is proposed to enhance impingement cooling with water droplets injection. However, previous studies were conducted on blade shower head film cooling, and less attention was given to the transition piece cooling. As a continuous effort to develop a realistic mist impingement cooling scheme, this paper focuses on simulating mist i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Comparison of the temperature and cooling effectiveness results is shown in Figure 3. From the reference [3,22], 5 μm is the optimized size of droplets which could provide a better heat transfer performance. The inner wall was each mode of three equally spaced regions.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the temperature and cooling effectiveness results is shown in Figure 3. From the reference [3,22], 5 μm is the optimized size of droplets which could provide a better heat transfer performance. The inner wall was each mode of three equally spaced regions.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, the equation is the same as in RNG model; however is not a constant and varies as a function of mean velocity field and turbulence (0.09 in log-layer ( / ) = 3.3, 0.05 in shear layer of ( / ) = 6). The equation is based on a transport equation for the meansquare vorticity fluctuation [14] as…”
Section: The Realizable − Model (Rke)mentioning
confidence: 99%
“…The CFD simulation models were employed and the results indicated that heat transfer effectiveness was improved with the rising hole's inclination and injection angle, since the thermal surface was impinged by more coolant directly. They [7], also investigated that jet flow with water drop promoted impinging cooling efficiency increasing. They concluded the mass of 3 × 10 −3 kg/s droplets with diameters of 5-35 µm could enhance the 90% cooling effectiveness and reduce 122 K of surface temperature.…”
Section: Introductionmentioning
confidence: 99%